Age and covid fatality. Issue 1 (1st January 2021) - Subramanian, S.
ABSTRACT: It is widely acknowledged that the distribution of Covid cases and that of Covid deaths by age constitute a factor that deserves to be taken into account in assessing and comparing quantitative indicators of Covid-related mortality. The single most widely employed measure of Covid mortality is the so-called Case Fatality Rate (CFR), which is just the ratio of Covid deaths to Covid cases. The CFR is essentially a measure of central tendency. The present note outlines a procedure, drawing on the standard literature on income inequality, for deriving a measure of Covid mortality which supplements information on average mortality with information on its dispersion across a population's age cohorts.